Re-strategizing communication in agricultural extension under devolution - Torres, Cleofe S. (The Philippine Journal of Development Communication, 2010)
The paper aimed to analyze the trends and gaps in communication strategies of the country's devolved agricultural extension service. Based on these, it recommends appropriate communication model and draws implications of the findings to UPLB's curricular, research, development, and extensions programs.